Competition driven nanocrystallization in high Bs and low coreloss Fe–Si–B–P–Cu soft magnetic alloys. (15th January 2015) - Sharma, Parmanand; Zhang, Xin; Zhang, Yan; Makino, Akihiro
Abstract : Based on experimental results and Johnson–Mehl–Avrami analysis, we have identified the nanocrystallization mechanism of newly developed Fe-rich Fe–Si–B–P–Cu soft magnetic alloys. Competition for growth among a large number of nuclei that are present in as-quenched state (grain density ∼3 × 10 21 m −3 ) and nucleated after annealing above the critical temperature for new nucleation (grain density ∼8 × 10 22 m −3 ) governs the grain size. A model of nanocrystallization is made to predict the magnetic/structural properties.